An Architecture for Self-adaptive Distributed Firewall - Costa Júnior, Edmilson P. da; Medeiros, Silas T.; Silva, Carlos Eduardo da; Madruga, Marcos (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2016: Anais do XVI Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2016.19318, 2016)
The notion of secure perimeter given by border firewalls ignores the possibility of attacks originating from inside the network. Although distributed firewalls allow the protection of individual hosts, the provided services might still be susceptible to attacks, as firewalls usually do not analyze application protocols. In this way, software vulnerabilities may be exploited until the problem has been fixed. From vulnerability discovery to the application of patches there is an exposure window that should be reduced. In this context, this paper presents an architecture for a distributed firewall system, in which a Vulnerability Assessment System is integrated for providing a self-adaptive mechanism capable of detecting vulnerabilities and executing actions to reduce exposure, contributing to mitigate the risk of vulnerability exploitation.